International human resource management - Dowling, Peter J. (Cengage-Learning, 2017)
Now in its seventh edition, 'International Human Resource Management' is established as a market leader that caters to students worldwide. This textbook has developed alongside the field - helping to shape what it is today - and remains a leading international human resources management (IHRM) textbook worldwide.